Correction to: Body size and genetic variation in the White-tipped Plantcutter (Phytotoma rutila: Cotingidae) suggest ecological divergence across the Chaco-Andes dry forest belt - Rodríguez Cajarville, María José (2019)
In the original publication of the article, there is a typo at the base text of Table 3 which is mentioned as “** robust result when critical c/h2 < 2 [following Brommer (2011)]”. However, the correct text should be “** robust result when critical c/h2 < 0.2 [following Brommer (2011)]”. The original article has been corrected.